Identification of species in the genus Nitraria L. (Nitrariaceae) based on nucleotide variability of nuclear ribosomal DNA - T. A. Poliakova; E. V. Banaev; M. A. Tomoshevich (Вавиловский журнал генетики и селекции)
Intragenomic polymorphism of ITS1 and ITS2 of nuclear ribosomal DNA sequences was analysed in 33 samples belonging to the Nitraria species N. schoberi, N. sibirica, and N. komarovii. The nucleotide variability of the ITS region was detected in the Nitraria species as single-nucleotide substitutions (mainly transitions) and single-nucleotide deletion. Information about the nucleotide variability of fragments is given for the first time by us. The ITS1-5.8S-ITS2 region contained 17 phylogenetically informative single-nucleotide polymorphisms. Eleven single-nucleotide substitutions (transitions, C/T) were detected in ITS1. The ITS2 spacer contained 273–274 bp and was more conservative. A total of 5 phylogenetically informative single-nucleotide polymorphisms (4 transitions: C/T, G/A, one transversion: G/C), one single-nucleotide deletion (T/–) were detected in ITS2. The average GC content was 61.5 %. The GC content was lower in N. sibirica (59.2 %) than in N. schoberi and N. komarovii (62.7 %). It has been shown that the shorter ITS2 is a suitable molecular marker separating these species, due to the low interspecific variability and simultaneous available intraspecific variability. Phylogenetic ML and BI trees constructed separately for the ITS1 and ITS2 spacers, as well as separately for the full-size ITS region and the ITS2 spacer, were congruent. The results obtained on the intraspecific differentiation of N. sibirica revealed two main ribotypes among the samples of this species: the main Siberian sibirica-ribotype and the main Kazakh sibiricaribotype. Geographical features of the distribution of N. sibirica ribotypes, as well as the presence of significant differences between the main Siberian and Kazakh sibirica-ribotypes (3 single-nucleotide substitutions) indicated significant inter-population differences and taxonomic heterogeneity of N. sibirica. Most likely, the processes of homogenization of nuclear ribosomal DNA of N. sibirica samples, the origin of which is associated with hybridization and speciation, are currently continuing.